2018
DOI: 10.1097/igc.0000000000001187
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Estrogen Receptor, Progesterone Receptor, and L1 Cell Adhesion Molecule Expression to Histology-Based Endometrial Carcinoma Recurrence Prediction Models: An ENITEC Collaboration Study

Abstract: Loss of ER and PR, and the presence of L1CAM are associated with high risk characteristics, and loss of PR is the strongest predictor of recurrent disease. Although a combination of these 3 markers is slightly superior to the traditional histological markers, a prognostic model including stage, PR expression, and LVSI is the most promising model in the identification of high risk carcinomas. In the stage I endometrioid carcinomas, PR immunohistochemistry appears to be of additional value in predicting recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 39 publications
4
51
2
Order By: Relevance
“…In fact, many articles have reported that the three factors are important predictors for endometrial cancer recurrence. 11 , 18 , 20 , 28 Especially, contrary to our impression, it seemed that patients who received adjuvant treatment had more recurrences than those who received none according to the hazard ratio in the univariate analysis. This might be explained by the fact that most of these patients who received adjuvant treatment had the later FIGO stages, with the high risk histotypes, which led to a strong “collinearity” between the adjuvant treatments and these high risk factors, 29 and the protective effect of adjuvant treatments was not enough to offset the high risk of recurrence incurred by these high risk factors.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In fact, many articles have reported that the three factors are important predictors for endometrial cancer recurrence. 11 , 18 , 20 , 28 Especially, contrary to our impression, it seemed that patients who received adjuvant treatment had more recurrences than those who received none according to the hazard ratio in the univariate analysis. This might be explained by the fact that most of these patients who received adjuvant treatment had the later FIGO stages, with the high risk histotypes, which led to a strong “collinearity” between the adjuvant treatments and these high risk factors, 29 and the protective effect of adjuvant treatments was not enough to offset the high risk of recurrence incurred by these high risk factors.…”
Section: Discussioncontrasting
confidence: 77%
“…ER and PR were considered positive when expression was seen in >5% of the tumor cells, which is the cut-off used in daily clinical practice for the characterization of breast cancer and which was shown to be valuable in endometrial carcinomas as well. 8 , 18 According to the 3-tier system for P53 immunohistochemistry interpretation, 19 the overexpression (the proportion of positive tumor cells ≥75%) and complete absence (the proportion of positive tumor cells was 0%) both considered as abnormal (aberrant/mutation-type), in contrast to the normal (wild-type) pattern with p53 expression levels in between these extremes (0–75%). Immunohistochemical parameters Ki67 was recorded as continuous variables based on the proportion of positive tumor cells (0–100%) ( Supplementary Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, besides the four immunohistochemical markers included in this study, markers like serum Ca125, CDK4/6, cytotoxic T cells, memory T cells, and L1CAM have demonstrated potential. [24][25][26][27] It is possible that more markers could contribute to a better prediction model. Another issue is that this model included patients with…”
Section: Discussionmentioning
confidence: 99%
“…Recently, [6,15,16,[27][28][29]31]. Previous studies have analyzed the relationship between L1CAM, p53, ER and PR, but focussed on prognostic rather than diagnostic capacity [7,32]. To our knowledge, this is the first study investigating the added value of IMP3 to L1CAM as diagnostic biomarker.…”
Section: Discussionmentioning
confidence: 99%